2022
DOI: 10.1038/s41598-022-08582-6
|View full text |Cite
|
Sign up to set email alerts
|

Bio-behavioral synchrony is a potential mechanism for mate selection in humans

Abstract: The decision with whom to form a romantic bond is of great importance, yet the biological or behavioral mechanisms underlying this selective process in humans are largely unknown. Classic evolutionary theories of mate selection emphasize immediate and static features such as physical appearance and fertility. However, they do not explain how initial attraction temporally unfolds during an interaction, nor account for mutual physiological or behavioral adaptations that take place when two people become attracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…We are not aware of any studies reporting differences in synchronisation performance between sexes, but previous research reported (1) advantage in males since adolescence in the motor timing task (attributed to faster motor learning) 41 and (2) enhanced spatio-temporal performance of males in a visuo-oculo-manual motor task (attributed to faster prediction process coupling target motion to a tracking hand) 42 . In a recent study 43 a novel piece of evidence emerged that heterosexual women report higher attraction to males who are ’super synchronisers’ during naturalistic socio-motor interaction (measured as level of coupling in body alignment), which suggests perhaps that there is a innate advantage in males, who are more attuned to sensori-motor signals. This interaction effect reaffirms the need for future experimental work to validate the main effects reported here, and to clarify the nature of the interaction between empathetic disposition and synchronisation performance, independent of emotional induction.…”
Section: Discussionmentioning
confidence: 99%
“…We are not aware of any studies reporting differences in synchronisation performance between sexes, but previous research reported (1) advantage in males since adolescence in the motor timing task (attributed to faster motor learning) 41 and (2) enhanced spatio-temporal performance of males in a visuo-oculo-manual motor task (attributed to faster prediction process coupling target motion to a tracking hand) 42 . In a recent study 43 a novel piece of evidence emerged that heterosexual women report higher attraction to males who are ’super synchronisers’ during naturalistic socio-motor interaction (measured as level of coupling in body alignment), which suggests perhaps that there is a innate advantage in males, who are more attuned to sensori-motor signals. This interaction effect reaffirms the need for future experimental work to validate the main effects reported here, and to clarify the nature of the interaction between empathetic disposition and synchronisation performance, independent of emotional induction.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 represents couples' synchrony scores arranged in ascending order. This approach to computing synchrony has been published in a series of previous works by our group as well as other researchers in the field Behrens, Snijdewint, et al, 2020;Dor-Ziderman et al, 2021;Golland et al, 2014Golland et al, , 2015Golland et al, , 2019Mauss et al, 2005;Zeevi et al, 2022).…”
Section: Descriptive Statistics and Preliminary Analysis: Supportive ...mentioning
confidence: 99%
“…This behavioral synchrony between potential partners in a mating context co-occurs with physiological synchrony. In a speed-dating experiment (Zeevi et al, 2022), couples with more synchronized electrodermal activity (a marker of autonomic arousal), were also more attracted to each other.…”
Section: Courtship: From Proximal To Interactivementioning
confidence: 99%